Ileal and jejunal Peyer’s patches in buffalo calves: Histomorphological comparison - Kritima Kapoor (Veterinary World, 2015)
Aim: The present study was aimed to elucidate the histomorphology of ileal and jejunal Peyer’s patches in the small intestine of buffalo calves and their structural comparison. Materials and Methods: The study was conducted on neonatal (n=10) and pre-pubertal (n=10) buffalo calves. The age of the postnatal buffalo calves was estimated by their temporary and permanent dentition. Results: The study revealed that several layers of oval to elongate elliptical lymphoid follicles were observed in submucosa on the anti-mesenteric side in the ileum of early neonatal calves. However, the follicles at this age, in jejunum were of all shapes present within one layer. The interfollicular space was occupied by the interfollicular tissue, which was diffuse and wider around jejunal lymphoid follicles as compared to ileal lymphoid follicles. However, toward the pubertal stage, the number of layers of lymphoid follicles was reduced in ileum due to involution while it remained similar in number in jejunum at this stage. Conclusion: The ileal Peyer’s patches were found to have started involution more or less around reaching puberty, whereas the jejunal Peyer’s patches appear to be functional throughout the lifespan of the animal.